Assessment of Acute Rejection by Global Longitudinal Strain and Cardiac Biomarkers in Heart-Transplanted Patients - Clemmensen, Tor Skibsted; Firooznia, Nilufar; Olawi, Fariha Morsal; Løgstrup, Brian Bridal; Poulsen, Steen Hvitfeldt; Eiskjær, Hans (Frontiers in Immunology, 2022)
Aims: To evaluate left ventricular global longitudinal strain (LVGLS), N-terminal pro brain natriuretic peptide (Nt-ProBNP) and Troponin T as non-invasive markers for acute cellular rejection (ACR) diagnosis and severity assessment after heart transplantation (HTx) Methods: We retrospectively included all HTx patients transplanted from 2013-2019. At each visit, the patients were subjected to endomyocardial biopsy (EMB), measurement of Nt-ProBNP and Troponin T and protocolled echocardiography with assessment of LVGLS. Sudden drop in graft function (SDGF) was defined as a drop in LVGLS ≥ -2% in combination with either an increase in Troponin T ≥ 20% or Nt-ProBNP ≥ 30% compared with levels at the latest visit. Results: We included 1436 EMBs from 83 HTx patients. The biopsies were grouped as 0R (n=857), 1R (n=538) and ≥2R (n=41). LVGLS was lower and Troponin T and Nt-ProBNP higher in the 2R group than in the 0R and 1R groups (LVGLS: -12.9±3.8% versus -16.9±3.1% and -16.1±3.3%; Troponin T: 79 [33;230] ng/L versus 27 [13;77] ng/L and 27 [14;68] ng/L; Nt-ProBNP: 4174 [1095;9510] ng/L versus 734 [309;2210] ng/L and 725 [305;2082], all p < 0.01). A SDGF was seen at 45 visits of which 19 had ≥2R ACR. EMBs showed ACR in 20 cases without SDGF. Finally, SDGF was neither seen nor did the EMB show rejection in 1136 cases. Thus, the sensitivity of SDGF for ≥2R ACR detection was 49% (32-65) and specificity 98% (97-99). The positive predictive value (PPV) was 42% (31-55) and the negative predictive value (NPV) 98% (98-99). The diagnostic value improved in a subanalysis excluding EMBs within 3 months after HTx, clinically interpreted false positive ≥2R ACR cases, and cases with ≥2R ACR who recently (<2 weeks) were treated with intravenous methylprednisolone due to ≥2R ACR (sensitivity 75% (48-93), specificity 97% (96-98), NPV 99% (99-100) and PPV 39% (27-52). Conclusions: Patients with ≥2R ACR have lower LVGLS and higher Troponin T and Nt-ProBNP than patients without 2R rejection. A non-invasive model combining changes in LVGLS and Troponin T or Nt-ProBNP showed excellent negative predictive value and moderate sensitivity and may be used as gatekeeper to invasive biopsies after HTx.